Patent Citations and the Geography of Knowledge Spillovers: Evidence from Inventor- and Examiner-added Citations - Thompson, Peter (The Review of Economics and Statistics, 2006)
I report new evidence for localized knowledge spillovers identified by within-patent variations in the geographic matching rates of citations added by inventors and citations added by examiners. Evaluated at the mean citation lag, inventor citations are 20 percent more likely than examiner citations to match the country of origin of their citing patent, while US inventor citations are 25 percent more likely to match the state or metropolitan area of their citing patent. The localization of intranational knowledge spillovers declines with the passage of time, but international borders present a persistent barrier to spillovers.